2012
DOI: 10.1016/j.bbabio.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent cold-induced fatty acid unsaturation, changes in membrane fluidity, and alterations in gene expression in Synechocystis

Abstract: Cold stress causes unsaturation of the membrane lipids. This leads to adjustment of the membrane fluidity, which is necessary for cold acclimation of cells. Here we demonstrate that the cold-induced accumulation of PUFAs in the cyanobacterium Synechocystis is light-dependent. The desA(-)/desD(-) mutant, that lacks the genes for Δ12 and Δ6 desaturases, is still able to adjust the fluidity of its membranes in spite of its inability to synthesize PUFAs and modulate the fatty acid composition of the membrane lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…The level of long chain fatty acids (C20) increased in proportion in 10 °C to 9.0% compared to 5.1% and 5.9% of 20 °C and 30 °C, respectively. These results correlate with previous studies that showed an increase in unsaturated fatty acid in response to low temperature to avoid a decrease in membrane fluidity182122. The increase of long chain fatty acids and PUFA levels in low-temperature conditions suggests changes in the structure of membrane-forming lipids, which changed to spatially larger forms to increase membrane fluidity21.…”
Section: Resultssupporting
confidence: 91%
“…The level of long chain fatty acids (C20) increased in proportion in 10 °C to 9.0% compared to 5.1% and 5.9% of 20 °C and 30 °C, respectively. These results correlate with previous studies that showed an increase in unsaturated fatty acid in response to low temperature to avoid a decrease in membrane fluidity182122. The increase of long chain fatty acids and PUFA levels in low-temperature conditions suggests changes in the structure of membrane-forming lipids, which changed to spatially larger forms to increase membrane fluidity21.…”
Section: Resultssupporting
confidence: 91%
“…Translating our findings for the different membranes into a biological context suggests that modulation of dimerization interfaces of transmembrane proteins can be achieved by changes of the lipid composition, which is a common stresses reaction [52,53,54]. Such dependence of protein action and membrane dynamics has for example been described for Hik33 [55,56,57] or DesK [58]. Furthermore, there are several reports that the transport or enzyme activity of proteins depends on the bilayer thickness or curvature (e.g., reviewed in [59]).…”
Section: Discussionmentioning
confidence: 59%
“…Cold stress leads to an increase of unsaturated fatty acids as membrane phospholipids [20]. It was demonstrated that cold induced increases in desaturation of fatty acids leads to the membrane fluidity that is essential for cold acclimation of cells [31]. It was suggested that cold stress induced changes in membrane lipids might play a significant role in the response and adaptation of cells to environmental change.…”
Section: Response To Proteome Changes At Low Temperaturementioning
confidence: 99%